The professional services firm bible - Baschab, John, 1968-; Piot, Jon, 1966- (John Wiley & Sons, 2005)
Spanning everything from legal firms and architects to fundraisers and dentists, the professional services industry continues to experience spectacular growth yet remains largely undocumented in business literature. Until now. The Professional Services Firm Bible is a sophisticated and comprehensive guide to running a highly productive professional services organization.